2020
DOI: 10.1093/molbev/msaa024
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Populations in Biofilms Contain More Persistent Plasmids

Abstract: Bacterial plasmids substantially contribute to the rapid spread of antibiotic resistance, which is a crisis in healthcare today. Coevolution of plasmids and their hosts promotes this spread of resistance by ameliorating the cost of plasmid carriage. However, our knowledge of plasmid–bacteria coevolution is solely based on studies done in well-mixed liquid cultures, even though biofilms represent the main way of bacterial life on Earth and are responsible for most infections. The spatial structure and the heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 58 publications
4
40
1
Order By: Relevance
“…This is the standard practise in the field, and previous studies have shown that plasmid fitness effects measured in laboratory conditions correlate with those measured in animal models 24 ; however, our results may not be fully representative of pOXA-48 fitness effects in the human gut. Future studies will need to explore more complex in vitro systems 60 , as well as in vivo animal models 61 . Another important limitation of our study is that we modelled bacterial communities with a simple resource competition model that does not consider spatial structure 62 , complex ecological interactions between community members 63 , plasmid-host co-evolution 64 , or differential rates of horizontal transmission 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This is the standard practise in the field, and previous studies have shown that plasmid fitness effects measured in laboratory conditions correlate with those measured in animal models 24 ; however, our results may not be fully representative of pOXA-48 fitness effects in the human gut. Future studies will need to explore more complex in vitro systems 60 , as well as in vivo animal models 61 . Another important limitation of our study is that we modelled bacterial communities with a simple resource competition model that does not consider spatial structure 62 , complex ecological interactions between community members 63 , plasmid-host co-evolution 64 , or differential rates of horizontal transmission 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In any case, PL3 persists over the long term much more effectively at low segregation levels (such as 10 −5 and 10 −6 ). In the present version of our model, the role of toxin-antitoxin postsegregational killing mechanisms in plasmid stabilization, eventually in synergy with spatial differentiation (biofilms), was not addressed ( 71 , 72 ), but we are signaling here the potential importance of this process in plasmid persistence and spread.…”
Section: Discussionmentioning
confidence: 99%
“…Besides investigating the impact of HGT for a range of different fitness effects, we have also shown how spatial structure is a key component for the emergence of HGT of rescuable genes. Both conjugation and transformation have indeed been observed to occur more frequently in biofilms than in well-mixed cultures (Madsen et al, 2012), and plasmids have furthermore been shown to be more persistent in biofilms (Stalder et al, 2020). On the other hand, spatial structure can slow down adaptation in asexual populations because individuals are mostly competing with their related conspecifics (Gordo and Campos, 2006;Habets et al, 2007;Chacón and Harcombe, 2019).…”
Section: Discussionmentioning
confidence: 99%